Behind the scenes of the Old Testament : cultural, social, and historical contexts - Greer, Jonathan S.; Hilber, John W. (John Walter); Walton, John H., 1952- (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2018)
"A team of world-class scholars covers the full range of Old Testament backgrounds studies in a concise, authoritative, and comprehensive manner"--
Introduction to historical geography / Paul Wright -- Regions and routes in the Levant / Carl G. Rasmussen -- Climate and environment of the Levant / Elizabeth Arnold -- Plants and animals of the land of Israel / Daniel Fuchs and Nimrod Marom -- Introduction to Biblical archaeology / Seymour Gitin -- Archaeology of the late Bronze Age / Joe Uziel -- Archaeology of the Iron Age I / Aren M. Maeir -- Archaeology of the Iron Age II / Amihai Mazar -- Archaeology of the Neo-Babylonian and Persian Periods / Constance E. Gane -- Archaeology of the Hellenistic Period / Jordan Ryan -- Introduction to ancient Near Eastern literature / Adam E. Miglio -- Hebrew inscriptions / Judith M. Hadley -- Mesopotamian literature / Dave C. Deuel -- Egyptian literature / Nili Shupak -- Hittite literature / Alice Mouton -- Northwest Semitic inscriptions / Margaret Cohen -- Ugaritic literature / William D. Barker -- Early Jewish literature / Ryan E. Stokes -- Introduction to ancient Near Eastern iconography / Izak Cornelius -- Egyptian iconography / Laura Wright -- Mesopotamian and Anatolian iconography / Daniel Bodi -- Canaanite/Israelite iconography / Brent A. Strawn -- The Ancestral Period / Richard S. Hess -- The Egyptian sojourn and the exodus / David A. Falk -- The Settlement Period / Pekka Pitknen -- The united monarchy / Steven M. Ortiz -- The divided monarchy: Israel / Jens Bruun Kofoed -- The divided monarchy: Judah / Eric L. Welch -- The exile and the exilic communities / Deirdre N. Fulton -- Persian Period / Yehud Ken Ristau -- The Maccabean Revolt and the Hasmonean Kingdom / Joel Willitts -- Akhenaten and the Amarna Period / Mark D. Janzen -- The late Bronze Age collapse and the sea peoples' migrations / Gregory D. Mumford -- Sheshonq's Levantine conquest and Biblical history / Yigal Levin -- The Battle of Qarqar and Assyrian aspirations / Mark Chavalas -- The Mesha inscription and relations with Moab and Edom / Juan Manuel Tebes -- The Tell Dan Inscription, Jehu's Revolt, and Aramaean campaigns in Israel and Judah / K. Lawson Younger Jr. -- Sennacherib's invasion of Judah and neo-Assyrian expansion / Kyle H. Keimer -- Eighth-century Levantine earthquakes and natural disasters / Ryan N. Roberts -- The Battle of Carchemish and seventh-century regional politics / Sara L. Hoffman -- Alexander the Great and Levantine Hellenism / Brent Sandy -- Monotheism in ancient Israel / Matthew J. Lynch -- Biblical texts studied in comparison with other ancient Near Eastern: documents / John H. Walton -- The temple in context / John H. Walton -- Priests in the ancient Near East / Gerald A. Klingbeil -- Worship, sacrifice, and festivals in the ancient Near East / Roy E. Gane -- Family religion in ancient Israel / Andrew R. Davis -- Prophecy, divination, and magic in the ancient Near East / John W. Hilber -- Death and burial in the Iron Age Levant / Christopher B. Hays -- Tribes and Nomads in the Iron Age Levant / Thomas D. Petter -- Women in Ancient Israel / Carol Meyers -- Family, Children, and Inheritance in the Biblical World / Victor H. Matthews -- Seasons, crops, and water in the land of the Bible / Oded Borowski -- Trade in the late Bronze and Iron Age Levant / Josh Walton -- Slavery in the world of the Bible / Richard E. Averbeck -- The local economies of ancient Israel / Peter Altmann -- Metallurgy in the world of the Bible / Brady Liss and Thomas E. Levy -- Ancient technologies of everyday life / Gloria London -- Food preparation in the Iron Age Levant / Cynthia Shafer-Elliott -- Feasting in the Biblical world / Janling Fu -- Music and dance in the world of the Bible / Annie Caubet -- Kingship and the state in ancient Israel / Nili S. Fox -- Social stratification in the Iron Age Levant / Avraham Faust -- Law and legal systems in ancient Israel / David W. Baker -- Wisdom Traditions in ancient Israel / Paul Overland -- Warfare in the world of the Bible / Mark Schwartz.
Includes bibliographical references (pages 515-593) and indexes.
Keywords: Bible. -- History of contemporary events; Middle East -- History -- To 622.; Middle East -- Civilization -- To 622.